CD163 and the FVIII/FXII ratio identified as novel biomarkers for early sepsis recognition - Yan, Nan; Diao, Yanjun; Zhou, Shan; Lu, Linhe; Chen, Chu; Zhu, Bingbing; Jia, Jingyuan; Liu, Jiayun (Frontiers in Medicine, 2026)
BackgroundSepsis is a systemic inflammatory syndrome caused by infection with certain pathogens. It includes sepsis, severe sepsis, and septic shock. In the intensive care unit (ICU), sepsis has a higher mortality rate. Therefore, early identification and management of sepsis can improve outcomes.ObjectiveAll the studies aimed to find out novel markers for early clinical recognition of sepsis.MethodsWe retrospectively analyzed 1,245 results of the detection of intrinsic coagulation factors (FVIII, FIX, FXI, and FXII). All the analysis results were visualized by the boxplot, Venn diagram, and circular barplot. After downloading three datasets from the Gene Expression Omnibus (GEO), differentially expressed genes (DEGs), common genes of the three datasets, Gene Ontology (GO), and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways enrichment analysis were analyzed and shown. Next, we screened hub genes. Finally, three receiver operating characteristic (ROC) curves were plotted separately for patients of three diseases versus 20 healthy normal subjects.ResultsOur analysis of 1,245 clinical specimens revealed that the co-occurrence of elevated FVIII (>150%) and reduced FXII (<50%) was most prevalent in three diseases: cirrhosis (n = 8), pneumonia (n = 5), and sepsis (n = 4). Multi-dataset screening identified 70 common differentially expressed genes. Protein–protein interaction network analysis pinpointed CD163 as the top hub gene (degree = 13). Critically, ROC analyses demonstrated that the FVIII/FXII ratio exhibited superior diagnostic performance for sepsis (AUC = 0.920), outperforming both FVIII (AUC = 0.710) and FXII (AUC = 0.840) alone.ConclusionCD163 and the FVIII/FXII ratio can be used as novel markers for early clinical recognition of sepsis.